Reeleição e reincidência de irregularidades orçamentárias nos municípios cearenses - Castelo, Sheila Karol Nunes de Lima (2018)
The present paper aims to identify the profile of the municipalities of Ceará that were fined fines by the Court of Auditors, due to nonconformities with the legislation. The results indicate that more populous municipalities, and with higher product tend to receive more fines, proportionally to GDP. On the other hand, the number of enrollments is negatively related to the penalties, suggesting that the more educated population exercises greater control over the public administration of the municipalities. Finally, the fact that the mayor was re-elected is the main determinant of the proportion of fines, indicating that the long-term permanence of the same group in power tends to favor the commission of infractions punishable.